Substantia nigra hyperechogenicity and Parkinson's disease risk in patients with essential tremor. Issue 4 (19th February 2016) - Sprenger, Fabienne S.; Wurster, Isabel; Seppi, Klaus; Stockner, Heike; Scherfler, Christoph; Sojer, Martin; Schmidauer, Christof; Berg, Daniela; Poewe, Werner
ABSTRACT: Background: Several studies have reported an increased risk for patients with essential tremor to develop Parkinson's disease. In addition, hyperechogenicity in the area of the substantia nigra has been associated with a markedly increased risk for Parkinson's disease. The objective of this study was to evaluate the validity of substantia nigra hyperechogenicity in patients with essential tremor as a risk marker for Parkinson's disease. Methods: Transcranial sonography was performed in 70 patients suffering from essential tremor. Fifty‐four of these patients were available for follow‐up after a mean of 6.16 ± 2.05 years and were assessed for the incidence of new‐onset Parkinson's disease. Results: The relative risk for developing Parkinson's disease in patients with essential tremor who had hyperechogenicity at baseline versus those without this hyperechogenicity was 7.00 (95% confidence interval, 1.62–30.34; sensitivity, 77.8%; specificity, 75.6%). Conclusions: Substantia nigra hyperechogenicity is also associated with an increased risk for Parkinson's disease in patients with essential tremor. These findings further support the potential role of this echofeature as a risk marker for Parkinson's disease. © 2016 Movement Disorder Society